American Association for the Surgery of Trauma–World Society of Emergency Surgery guidelines on diagnosis and management of abdominal vascular injuries. Issue 6 (December 2020) - Kobayashi, Leslie; Coimbra, Raul; Goes, Adenauer M.O.; Reva, Viktor; Santorelli, Jarrett; Moore, Ernest E.; Galante, Joseph M.; Abu-Zidan, Fikri; Peitzman, Andrew B.; Ordonez, Carlos A.; Maier, Ronald V.; Di Saverio, Salomone; et al.
Abstract : ABSTRACT: Abdominal vascular trauma accounts for a small percentage of military and a moderate percentage of civilian trauma, affecting all age ranges and impacting young adult men most frequently. Penetrating causes are more frequent than blunt in adults, while blunt mechanisms are more common among pediatric populations. High rates of associated injuries, bleeding, and hemorrhagic shock ensure that, despite advances in both diagnostic and therapeutic technologies, immediate open surgical repair remains the mainstay of treatment for traumatic abdominal vascular injuries. Because of their devastating nature, abdominal vascular injuries remain a significant source of morbidity and mortality among trauma patients. The American Association for the Surgery of Trauma in conjunction with the World Society of Emergency Surgery seek to summarize the literature to date and provide guidelines on the presentation, diagnosis, and treatment of abdominal vascular injuries. LEVEL OF EVIDENCE: Review study, level IV.